Comparative evaluation of a new magnetic bead-based DNA extraction method from fecal samples for downstream next-generation 16S rRNA gene sequencing. - Kara D McGaughey; Tulay Yilmaz-Swenson; Nourhan M Elsayed; Dianne A Cruz; Ramona R Rodriguez; Michael D Kritzer; Angel V Peterchev; Megan Gray; Samantha R Lewis; Jeffrey Roach; William C Wetsel; Douglas E Williamson (PLoS ONE, 2018)
We are colonized by a vast population of genetically diverse microbes, the majority of which are unculturable bacteria that reside within the gastrointestinal tract. As affordable, advanced next-generation sequencing technologies become more widely available, important discoveries about the composition and function of these microbes become increasingly possible. In addition to rapid advancement in sequencing technologies, automated systems have been developed for nucleic acid extraction; however, these methods have yet to be widely used for the isolation of bacterial DNA from fecal samples. Here, we adapted Promega's Maxwell® RSC PureFood GMO and Authentication kit for use with fecal samples and compared it to the commonly used Qiagen QIAamp® PowerFecal® kit. Results showed that the two approaches yielded similar measures of DNA purity and successful next-generation sequencing amplification and produced comparable composition of microbial communities. However, DNA extraction with the Maxwell® RSC kit produced higher concentrations with a lower fecal sample input weight and took a fraction of the time compared to the QIAamp® PowerFecal® protocol. The results of this study demonstrate that the Promega Maxwell® RSC system can be used for medium-throughput DNA extraction in a time-efficient manner without compromising the quality of the downstream sequencing.